The Business of Product Innovation : International Empirical Evidence - Lederman, Daniel (2012)
It is so widely recognized that innovation is a key driver of economic growth that it is cliché to say so. This article studies product innovation by firms with data from 68 countries, covering more than 25,000 firms in eight manufacturing sectors. The author assesses the predictions of inter-disciplinary research on innovation by firms. The econometric evidence suggests that globalization and local knowledge increase the likelihood that firms will introduce new products. By contrast, domestic regulatory impediments to competition are not robustly correlated with product innovation.